Neutrophils as a potential therapeutic target in Alzheimer’s disease - Aries, Michelle L.; Hensley-McBain, Tiffany (Frontiers in Immunology, 2023)
Alzheimer’s disease (AD) is the leading cause of dementia in the United States. Sporadic or late-onset AD remains incompletely understood, with age as the current greatest risk factor. Inflammation in general and neutrophils, a potent mediator of inflammation, have been shown to exacerbate AD associated dementia. This review explores the latest research on neutrophils in AD mouse models and in human cohort studies and discusses current gaps in research and needs for future studies. AD mouse models have shown neutrophil chemotactic migration towards amyloid beta plaques in the brain. Capillary blood flow stalling decreases blood perfusion to associated brain regions and mouse studies have demonstrated that anti-Ly6G antibodies lead to a decrease in capillary blood flow stalling and memory improvement. Several recent transcriptomic studies of blood and brain tissue from persons with AD have shown an upregulation in neutrophil-related genes, and studies have demonstrated neutrophil involvement in brain capillary adhesion, blood brain barrier breaching, myeloperoxidase release, and the propensity for neutrophil extracellular trap release in AD. Neutrophil-derived inflammation and regulation are a potential potent novel therapeutic target for AD progression. Future studies should further investigate neutrophil functionality in AD. In addition, other aspects of AD that may impact neutrophils including the microbiome and the APOE4 allele should be studied.